SMART VEHICLE MONITORING AND ANALYSIS SYSTEM WITH IOT TECHNOLOGY - A. Hamid, A. Hadi Fikri; Chang, Kah Weng; A. Rashid, Rozeha; Mohd, Alias; Abdullah, M. Shahidan; Sarijari, M. Adib; Abbas, Mazlan (International Journal of Integrated Engineering, 2019)
In order to reduce the increasing number of road accidents in recent years, the Transport Ministry of Malaysia is keen to study the flexible road tax payment system based on the motorists’ driving behavior which can be monitored using a vehicle monitoring system. However, existing vehicle monitoring systems in the market mostly rely only on Global Positioning System (GPS) to estimate the vehicle’s speed and location which results may be inaccurate once the satellite coverage is lost due to tall buildings or dense forest. Therefore, a Smart Vehicle Monitoring and Analysis System (VMAS) using Internet of Things (IoT) technology is proposed. The developed system comprises of an Android application on smartphone, an On-board Diagnostics II (OBD-II) device and a cloud database management system. OBD-II device will collect real-time data on engine parameters. The data will be automatically extracted using Bluetooth connection to the Android platform for display and to upload data to the cloud server. The cloud server is used for data storage and can be accessed remotely by authorized or administrative personnel via a monitoring webpage. It will provide complete visibility of uploaded data in real time as well as instant activities reports and history logs. The performance investigation shows that the system latency is around 1 second. The data analysis includes driving attributes ranking and fuel efficiency rating which is foreseen to contribute significantly to flexible road tax scheme and diagnostic tests by vehicle manufacturers respectively.